The Role Of Social Media Tiktok In Increasing The Interest In Entrepreneurship In The Millenial Generation - Ramayanti Simanjorang; Zuhrinal M Nawawi (Journal of Business, Social and Technology, 2022)
At this time the world has entered the industrial revolution 4.0, where all life activities are based online. The advancement of the world of technology today requires the internet as a means of communication, data exchange, and information seeking media which is in great demand by every group, especially the millennial generation. This study aims to determine the role of tiktok social media in increasing interest in entrepreneurship in the millennial generation. The method that the researcher uses in this study is a descriptive qualitative research method by conducting interviews with 10 informants who have a TikTok account with more than 800 followers. The results of the interview show that TikTok plays a role in increasing interest in entrepreneurship in the millennial generation as a promotional medium and a forum for selling online. so there is no need to meet directly with consumers. That way, the millennial generation doesn't have to spend a lot of money to make brochures, and they don't have to rent an expensive place to sell.